2020
DOI: 10.1002/aocs.12340
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of Novel Nanostructured Lipid Carriers with Photoprotective Properties Made from Carnauba Wax, Beeswax, Pumpkin Seed Oil, and UV Filters

Abstract: Pumpkin seed oil (PSO) with carnauba wax and beeswax was used to develop nanostructured lipid carriers (NLC) loaded with a UV filter, Uvinul ® A Plus B. The aims of the study were to optimize the concentration of PSO to develop a stable NLC formulation, determine storage stability of the NLC with and without PSO, and the synergistic effect of PSO-NLC with UV filter for photoprotective properties. The physical properties of NLC were optimized based on the mean particle size, polydispersity index, and storage st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
(69 reference statements)
1
6
0
Order By: Relevance
“…The melting temperature of the constituents was corroborated with typical values reported in the literature, namely curcumin at 175.4 °C [19,62], beeswax at 68.4 °C [63] and carnauba wax at 86.8 °C [64]. It was observed that MP1 series which include CMP1, MP1 and PM1 showed the highest T m values (comparing with the other series), being close to that of beeswax, the only lipid present in the mixture composition.…”
Section: Samplesupporting
confidence: 84%
“…The melting temperature of the constituents was corroborated with typical values reported in the literature, namely curcumin at 175.4 °C [19,62], beeswax at 68.4 °C [63] and carnauba wax at 86.8 °C [64]. It was observed that MP1 series which include CMP1, MP1 and PM1 showed the highest T m values (comparing with the other series), being close to that of beeswax, the only lipid present in the mixture composition.…”
Section: Samplesupporting
confidence: 84%
“…The data were analyzed using Malvern Zetasizer (ZS90, Malvern Instruments, UK). [28][29] The data analysis was operated at a wavelength of 633 nm at 25°C and a scattering angle of 90°. The size distribution was indicated by the intensity distribution.…”
Section: Characterizationsmentioning
confidence: 99%
“…Therefore, antioxidants with potential UV absorbing activity may be promising to be added in sunscreen formulation to boost up the effect of UV filters. According to the previous studies, the findings indicated the additional value of antioxidants in sunscreen development to enhance the photoprotective properties while maintaining antioxidant capacity (Chu et al, 2019, 2020; Chu, Azizul Hasan, et al, 2021; Lacatusu et al, 2014). Also, Chu et al (2019) and Badea et al (2016) claimed the synergistic interaction that occurred among the sunscreen active compounds with different seed oils to boost up the photoprotection.…”
Section: Nonprescription Over‐the‐counter Sunscreen Drug and The Role Of Seed Oil In Sunscreenmentioning
confidence: 84%
“…The study from Bardaa et al (2016) showed significant wound healing effect of pumpkin seed oil in animal assays through topical application. Apart from that, Chu et al (2020) reported pumpkin seed oil in nanostructured lipid carrier development for sunscreen formulation development demonstrated synergistic effect from pumpkin seed oil and synthetic UV filters. Pumpkin seed oil showed the effect in boosting the UV protection of a sunscreen formulation (Chu et al, 2020).…”
Section: Potential Seed Oils In Sunscreen Developmentmentioning
confidence: 99%
See 1 more Smart Citation